SCHOOL UNIFORM IN MODERN SOCIETY - San’atova, Malika Kahramonovna; Bahronova, Zarinabonu Bahriddinovna; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
Over the past few years, the Ministry of Education has been increasingly raising the issue of introducing uniform school uniforms in Uzbekistan. The advantage of introducing a single standard of clothing for students by educational institutions will highlight this material.